Voting behavior in the South Korean presidential election – exploring the regional voting pattern. Issue 3 (8th July 2019) - Kim, Tae Wan
Abstract : Purpose: The purpose of this paper is to examine regional voting patterns in South Korea using the results from six presidential elections since the 1990s. Design/methodology/approach: A χ 2 test was used to determine the municipalities where a regional voting pattern emerged, and λ correlation coefficients were calculated to examine changes in the regional voting patterns. Findings: The analyses lead to three key findings. First, voting patterns differ in Yeongnam and Honam: regional voting in Yeongnam is getting weaker, it remains strong in Honam. Second, the tendency to vote along regional lines decreased significantly in the election in which the Honam party fielded a candidate with a Yeongnam appeared identity. Third, regional voting patterns declined but then stabilized at a constant level, regardless of the candidates' local identity, which was confirmed in "Bu-Ul-Gyeong." Originality/value: This paper can empirically verify the manifestation of regional voting pattern and confirm the trend. It is possible to derive a condition for suppressing the regional voting pattern.